2016
DOI: 10.1177/1010539516651957
|View full text |Cite
|
Sign up to set email alerts
|

Work Ability and Its Related Factors Among Workers in Small and Medium Enterprises

Abstract: Work ability is related to many factors that might influence one's capacity to work. This study aimed to examine the work ability and its related factors among small and medium enterprises (SME) workers in 4 Association of Southeast Asian Nations (ASEAN) countries. The participants in this study included 2098 workers from food and textile industries in Indonesia, Malaysia, Thailand, and Vietnam. A cross-sectional survey of anonymous self-administrated questionnaire was designed to collect information on sociod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…Microentrepreneurs are an under-researched population in terms of recovery from work and work ability [9,10,42,73], and thus this intervention study will be unique and provide important information that can be used in developing services for and studying microentrepreneurs. This study adapts an intervention to a very specific target group which could be a fruitful route to enlarge the reach of health promotion interventions compared to one-fitsall strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microentrepreneurs are an under-researched population in terms of recovery from work and work ability [9,10,42,73], and thus this intervention study will be unique and provide important information that can be used in developing services for and studying microentrepreneurs. This study adapts an intervention to a very specific target group which could be a fruitful route to enlarge the reach of health promotion interventions compared to one-fitsall strategies.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have been published on the factors associated with work ability among microentrepreneurs [9,10]. Cross-sectional studies have found good planning and control over work; flexibility at work; good social support from family, friends and other entrepreneurs; and regular exercise to be associated with maintaining entrepreneurs' good health [11].…”
Section: Introductionmentioning
confidence: 99%
“…The Thai version of WAI has been tested for validity. 14 A number of studies among different groups of Thai populations reveal the relation between individual and work-related factors with WAI, 15,16 but it has not yet been studied among international migrant workers in Thailand.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Kaewboonchoo et al found that SMEs in ASEAN countries, including Indonesian, face a number of difficulties in complying with OHS regulations due to fewer resources and less awareness [1]. The working environment and ergonomic conditions in SMEs may not be well controlled and maintained and have the high possibility of affecting the workers' health.…”
Section: Introductionmentioning
confidence: 99%
“…Even if current OHS laws cover SME workers, there still is a lack of implementation [1]. Susilowati et al found that the education level among SME workers was low, as most of them only graduated from junior high school, which led the researches to determine that the government should conduct a worker-based workplace health promotion approach to facilitate their understanding in OHS socialization and improve OHS implementation [2].…”
Section: Introductionmentioning
confidence: 99%